2018
DOI: 10.3389/fgene.2018.00277
|View full text |Cite
|
Sign up to set email alerts
|

HLA Pharmacogenetic Markers of Drug Hypersensitivity in a Thai Population

Abstract: Severe cutaneous adverse drug reactions (SCARs) including Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and drug reactions with eosinophilia and systemic symptoms (DRESS) are potentially life-threatening cutaneous reactions caused by several drugs. Recently, a number of genes encoding for human antigen presenting proteins, HLA alleles, have been discovered as valid pharmacogenetic markers for prediction of these life-threatening reactions. This study was aimed to determine the distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
(72 reference statements)
2
19
1
Order By: Relevance
“…The most frequent HLA-A alleles found in this study were A * 11:01:01 and A * 24:02:01. The high frequency of HLA-A * 11:01 and A * 24:02:01 is consistent with previous typing results of northern Kinh Vietnamese and other Asian populations, such as the Chinese, Thai, Indonesian, Korean, and Japanese (Lee et al, 2005;Hoa et al, 2008;Yuliwulandari et al, 2009;Shen et al, 2014;Ikeda et al, 2015;Nakkam et al, 2018). Among HLA-C alleles identified in this study, C * 07:02:01 was found to be widely distributed globally, while C * 01:02:01 was common in Asians (Lee et al, 2005;Shen et al, 2014;Ikeda et al, 2015;Nakkam et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The most frequent HLA-A alleles found in this study were A * 11:01:01 and A * 24:02:01. The high frequency of HLA-A * 11:01 and A * 24:02:01 is consistent with previous typing results of northern Kinh Vietnamese and other Asian populations, such as the Chinese, Thai, Indonesian, Korean, and Japanese (Lee et al, 2005;Hoa et al, 2008;Yuliwulandari et al, 2009;Shen et al, 2014;Ikeda et al, 2015;Nakkam et al, 2018). Among HLA-C alleles identified in this study, C * 07:02:01 was found to be widely distributed globally, while C * 01:02:01 was common in Asians (Lee et al, 2005;Shen et al, 2014;Ikeda et al, 2015;Nakkam et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Among HLA-C alleles identified in this study, C * 07:02:01 was found to be widely distributed globally, while C * 01:02:01 was common in Asians (Lee et al, 2005;Shen et al, 2014;Ikeda et al, 2015;Nakkam et al, 2018). The predominance of HLA-B * 15 alleles is a major distinguishing characteristic of the Kinh population from the Thai and Chinese groups (Shen et al, 2014;Nakkam et al, 2018). However, this predominance is similar in the Indonesian population (Yuliwulandari et al, 2009).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…New genetic associations in DHRs have been found (Table ): HLA‐B*13:01‐restricted CD8 + T‐cell responses to dapsone and nitroso dapsone in Thai and Han Chinese populations ; this allele together with HLA‐B*56:02/04, CYP2C19*3 and omeprazole co‐medication, in phenytoin‐induced DRESS ; CYP2C19*3 and having Chinese ancestry for SJS ; HLA‐A*24:02 in anticonvulsant‐induced SCARs in Han Chinese ; HLA‐A*32:01 in vancomycin‐induced DRESS in a European ancestry population ; HLA‐B*35:05 allele correlates nevirapine patch test results ; and HLA‐B*48:01 with IR and HLA‐C*04:06, HLA‐C*08:01 and HLA‐DRB1*04:06 with NIR on BL reactions in Thai children . Finally, an extensive study in Thai population has revealed the existence of high prevalence (HLA‐B*13:01 for dapsone; HLA‐B*15:02 for carbamazepine and oxcarbazepine; HLA‐B*58:01, HLA‐A*33:03 and HLA‐C*03:02 for allopurinol; HLA‐C*08:01, HLA‐C*14:02 and HLA‐DRB1*12:02 for co‐trimoxazole) and low prevalence (HLA‐B*57:01 for abacavir, and HLA‐B*56:02/HLA‐B*56:04 for phenytoin) of pharmacogenetic markers of drug‐induced SCARs . These differences mark the cost‐effectiveness of the screening of these markers to prevent SCARs prior to prescription of some drugs in specific populations.…”
Section: Risk Factorsmentioning
confidence: 99%